(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The job readiness of vocational high school (SMK) graduates remains a challenge because not all students have adequate work experience and placement support to meet the demands of the industrial world. This study aims to analyze the influence of fieldwork experience (PKL) and the role of the Special Job Exchange (BKK) on student job readiness. The study used a quantitative approach with a survey design conducted at SMK PGRI 1 Tulungagung. The study population was all grade XII students, with a sample of 94 respondents selected using probability sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS. The results showed that PKL experience had a positive and significant effect on job readiness (t = 5.112; p < 0.001), as did the role of BKK which also had a positive and significant effect (t = 5.430; p < 0.001). Simultaneously, both variables had a significant effect on student job readiness (F = 74.102; p < 0.001). The adjusted R² value of 0.611 indicates that the internship experience and the role of the BKK can explain 61.1% of the variation in work readiness, while 38.9% is influenced by other factors outside the study. This finding confirms that learning experiences in the world of work supported by the optimization of the BKK function play a significant role in improving the work readiness of vocational high school students to enter the workforce